Electrochemical performance investigation of electrospun urchin-like V2O3-CNF composite nanostructure for vanadium redox flow battery. (10th March 2017) - Busacca, C.; Di Blasi, O.; Briguglio, N.; Ferraro, M.; Antonucci, V.; Di Blasi, A.
Abstract: Home-made electrospun catalyst based on urchin-like vanadium (III) oxide-carbon nanofiber (V2 O3 -CNF) composite is synthesized from a solution containing vanadium (V) oxytriisopropoxide VO-(OiPr)3 as metal oxide precursor and polyvinylpyrrolidone (PVP) as carbon source for vanadium redox flow battery (VRFB) application. X-ray diffraction (XRD) as well as scanning electron microscopy (SEM) analysis show a typical V2 O3 rhombohedral structure and an urchin-like V2 O3 -CNF morphology, respectively. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) measurements show a high electrocatalytic activity for the composite electrospun samples both in terms of peak to peak separation (ΔE = 0, 02 V) and lower charge transfer resistance (Rct = 0.12 ohm cm 2 ) with respect to a pristine CNF. The better reversibility is ascribed to the oxygen functional groups presence that act as catalytic sites reducing kinetic overpotentials. Moreover, thanks to the rhombohedral structure of V2 O3, as well as to the more graphitic structure of the carbon, a suitable electrical conductivity is guaranteed for reducing ohmic overpotentials.